E-readiness of turkish SMEs : the role of external factors - Özparlak, Melih (My University, 2005)
TÜRK KOBİ'LERİNİN E-DÖNÜŞÜME HAZIR OLMASINDA DIŞSAL FAKTÖRLERİN ETKİSİ Bu çalışma, 'e-Hazırlık' kavramını ve KOBİ'leri e-Dönüşüme hazır hale getiren dışsal faktörlerin etkisini incelemek üzere yapılmıştır. Bilgisayar ve internet teknolojileririnin giderek yoğun bir şekilde kullanılmaya başlandığı bu yeni iş ortamında KOBİ'leri bu ortama hazırlayacak dışsal faktörler; Devlet, Bankacılık Sektörü, Altyapı, Ticareti Destekleyen Organizasyonlar ve Tüketicileri, Kişileri ve İnsan Kaynağını kapsayan Toplum olarak ele alınmıştır. Bu doğrultuda, Türk KOBİ'lerini kapsayan bir örneklem grubuyla bir saha çalışması yürütülerek bu dışsal faktörlerin etkisi ortaya konmuştur.

E-READINESS OF TURKISH SMEs: THE ROLE OF EXTERNAL FACTORS This study focuses on the concept of e-readiness and the external factors which may encourage small and medium scaled enterprises (SMEs) to become prepared for the new business environment in which the internet and the information and communication technologies are increasingly used. The study mainly investigates the external factors rather than the organizational and pre-conditional ones. Therefore, the effect of the government, the financial sector, the infrastructure, the trade promoting organizations, the consumers and the human capital are taken into consideration within a survey, conducted among a sample population of Turkish SMEs. The purpose of the survey is to expose the possible effects of these factors by obtaining the opinions of the SME management staffs.
Keywords: Bilişim Teknolojileri; e-Dönüşüm; e-İşletme; e-Ticaret; Küçük İşletmeler